Locating Lost Gifts: Terracotta Figurines as Evidence for Ephemeral Offerings - Kopestonsky, Theodora (Journal of Greek Archaeology, 2018)
For the most part, Greek gods were not altruistic or loving. In order to get something, one needed to coerce, manipulate, or even bribe a god. Although there was no guidebook to ritual practice or a standardized belief system in ancient Greece, certain rites were repeated in similar ways at multiple locations by different people. Offering a gift to a god was one of these fundamental, and common, actions in Greek ritual practice.